Toward Resilient Networks: AI and Deep Learning Strategies for Intrusion Detection - Marthalia, Lia (Indonesian Scientific Publication, 2025)
As cyber threats become more sophisticated and pervasive, the demand for advanced Network Intrusion Detection Systems (NIDS) has increased dramatically. This narrative review investigates the application of Artificial Intelligence (AI) and Deep Learning (DL) techniques in enhancing NIDS performance, aiming to address the limitations of conventional rule-based systems. The literature was systematically retrieved from reputable databases such as Scopus and IEEE Xplore using keywords including